Learning to Do Fieldwork through Role-Playing: A Class Experiment - Sordi, Adele Del (Gamevironments, 2021)
Social scientists use fieldwork research to collect data to understand, observe, and interact with people in their natural settings. Most researchers learn fieldwork methods by doing and find that, however valuable, the publications on the subject are a poor substitute for the actual experience. So how can students and young researchers acquire these skills when limited time, lack of funding or a global pandemic prevent them from reaching the field? The game introduced here proposes to teach fieldwork practices through immersive role-playing. Game participants assume the roles of social scientists and have to complete their research projects by overcoming a series of typical fieldwork challenges, from making the appropriate preparations to finding respondents, from conducting interviews to treating data correctly and facing emergencies. Played for the first time with a group of undergraduate students at the Ludwig Maximilian University of Munich, the game constitutes a safe, easy, and cost-effective way to familiarize young researchers with the methods and difficulties of field research.